Supporting and Encouraging Writing - Alison Farrell; Katrin Girgensohn; Jolanta Sinkuniene (Educare)
COST Action 15221 (Advancing effective institutional models towards cohesive teaching, learning, research and writing development) strives to create synergy among supports for four crucial components of academic career – teaching, learning, research and writing.